The Effect of Extra Functional Exercises with and without Functional Muscle Stimulation on the Lumbar Lordosis in Women Aged 20-30 Years in Tabriz - Amir Ghiami rad; Solmaz Jafari Amirkhiz; Behnam Shahbazi (Islamic Azad University, Hamedan Branch, 2023)
Objective Increased lordosis in the lumbar is one of the causes of poor posture and back pain. The purpose of this research is to investigate the effectiveness of extra-functional exercises with and without functional stimulation of the muscles around the lumbar joints in women with increased lumbar lordosis. Methods The conducted research is quasi-experimental and applied. The statistical population consisted of 46 women divided into two equal groups within the age group of 20 to 30 years in Tabriz city, each having a lordosis angle of 40 degrees. Evaluation of lordosis angles (control and experimental groups) was measured using a flexible ruler, tilt meter, and McGill test (pre-test). Then, for 6 weeks, the experimental group performed three sessions of exercise protocol and muscle functional stimulation per week, while the control group only received exercises similar to those of the experimental group (post-test). Statistical analysis was conducted using independent t-tests and paired t-tests at a significance level of 0.05. Results In the experimental group compared to the control group, there was a significant difference in lumbar lordosis and anterior pelvic tilt components in the post-test (P<0.05). Conclusion Based on the obtained results, it can be acknowledged that central stability exercises (Extra Functional) along with muscle functional stimulation can yield beneficial results in improving lumbar biomechanics in cases of lordosis and hyperlordosis disorders within the statistical population.